Ferrite carrier core material, and electrophotographic development carrier and electrophotographic developer using the same

The ferrite carrier core material with controlled composition and charge properties addresses development memory and developer transfer issues, enabling stable high-quality image formation in electrophotographic processes.

JP7601564B2Active Publication Date: 2024-12-17DOWA ELECTRONICS MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020087366
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-19
Publication Date
2024-12-17
Estimated Expiration
2040-05-19

AI Technical Summary

Technical Problem

Existing electrophotographic carrier core materials face issues with development memory and insufficient developer transfer due to increased surface roughness, leading to reduced developer amounts on the developing roller and in the development area.

Method used

A ferrite carrier core material with a specific composition (Mn x Mg y )Fe 3-(x+y)O 4, containing 0.1

Benefits of technology

The solution effectively suppresses development memory and maintains stable developer transfer, ensuring high-quality image formation over extended use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601564000007
    Figure 0007601564000007
  • Figure 0007601564000001
    Figure 0007601564000001
  • Figure 0007601564000002
    Figure 0007601564000002
Patent Text Reader

Abstract

To provide a carrier core material that can suppress development memory, and also is unlikely to cause reduction in pump-up amount of a developer to a development roller and a transport amount of the developer to a development region.SOLUTION: A ferrite carrier core material has a composition expressed by (MnxMgy)Fe3-(x+y)O4 (where 0.1<x≤1, 0.1<y≤1), in which Ca is contained within a range of more than 0.10 mol% and less than 1.0 mol% with respect to the total number of mols of Mn, Mg and Fe, and a charge amount of the carrier core material is 18 μC / g or more. Here, a maximum mountain valley depth Rz of the particles of the carrier core material is preferably 1.4 μm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferrite carrier core material, and a carrier for electrophotographic development and a developer for electrophotography each using the same. [Background technology]

[0002] For example, in image forming devices using electrophotography such as facsimiles, printers, and copiers, a toner is attached to an electrostatic latent image formed on the surface of a photoconductor to make it visible, and this visible image is transferred to paper or the like, and then fixed by applying heat and pressure. From the viewpoint of achieving high image quality and colorization, so-called two-component developers containing a carrier and a toner are widely used as developers.

[0003] In a development method using a two-component developer, the carrier and toner are mixed and stirred in a development device, and the toner is charged to a predetermined amount by friction. The developer is then supplied to a rotating development roller, a magnetic brush is formed on the development roller, and the toner is electrically transferred to the photoconductor via the magnetic brush, making the electrostatic latent image on the photoconductor visible. After the toner transfer, the carrier remains on the development roller and is mixed with the toner again in the development device. For this reason, the carrier is required to have the following characteristics: transfer characteristics to the development roller (pumping ability), magnetic characteristics to form a magnetic brush, charging characteristics to impart the desired charge to the toner, and durability in repeated use.

[0004] Such carriers are generally made of magnetic particles such as magnetite and various ferrites, the surfaces of which are coated with resin. The magnetic particles serving as the carrier core material are required to have good magnetic properties as well as good triboelectric properties with respect to the toner. Various shapes of carrier core materials that satisfy such properties have been proposed.

[0005] For example, in order to suppress development memory (the phenomenon in which the influence of a previous image appears in a subsequent image), it has been proposed to use manganese (Mn) ferrite particles containing specific amounts of strontium (Sr) and silicon (Si) and having a specific range of maximum peak-valley depth Rz and its standard deviation σ as a carrier core material (Patent Document 1).Furthermore, ferrite core materials with extremely deformed shapes such as a rock candy shape and / or an oyster shell shape have also been proposed (Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-031031 A [Patent Document 2] JP 2007-148452 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, by increasing the maximum peak-valley depth Rz of the particle, in other words, by promoting the unevenness of the particle surface, when the surface of the carrier core material is resin-coated, part of the carrier core material is exposed to the surface, reducing the electrical resistance of the resin-coated carrier and suppressing the occurrence of development memory to some extent, but there is a risk that the amount of developer pumped up to the developing roller and the amount of developer transported to the development area will be insufficient.

[0008] The present invention has been made in consideration of these conventional problems, and its purpose is to provide a carrier core material that can suppress development memory and is less likely to cause a decrease in the amount of developer picked up by the developing roller and the amount of developer transported to the development area.

[0009] Another object of the present invention is to provide a carrier for electrophotographic development and a developer for electrophotography which are capable of stably forming images of good quality even after long-term use. [Means for solving the problem]

[0010] The ferrite carrier core material according to the present invention for achieving the above object (hereinafter, may be simply referred to as "carrier core material") is (Mn x Mg y )Fe 3-(x+y) O4 (where 0.1 < x ≤ 1, 0.1 < y ≤ 1), and is a ferrite carrier core material having a composition represented by the formula, and contains Ca in a range of more than 0.10 mol% and less than 1.0 mol% with respect to the total number of moles of Mn, Mg, and Fe, and is characterized in that the charge amount is 18 μC / g or more.

[0011] Here, in the carrier core material having the above configuration, it is preferable that the maximum valley depth Rz of the particles is 1.4 μm or more.

[0012] Further, according to the present invention, there is provided an electrophotographic developer characterized in that the surface of the carrier core material described above is coated with a resin.

[0013] And further, according to the present invention, there is provided an electrophotographic developer characterized by containing the electrophotographic developer carrier described above and toner.

[0014] The charge amount of the carrier core material in the present invention is measured by the following method. 9.5g of carrier core material and 0.5g of toner from a commercially available full-color machine are placed in a 100ml glass bottle with a stopper, and left for 12 hours in an environment with a temperature of 25°C and a relative humidity of 50% to condition the humidity. The conditioned carrier core material and toner are mixed by shaking with a shaker for 30 minutes. Here, the shaker used was a NEW-YS type made by Yayoi Co., Ltd., and was performed at 200 times / min and an angle of 60°. 500mg of the mixed carrier core material and toner were weighed, and the charge amount was measured with a charge amount measuring device. The charge amount measuring device used was the "STC-1-C1 type" made by Nippon Piotek Co., Ltd., with a suction pressure of 5.0kPa and a suction mesh made of SUS 795mesh. Two measurements were taken for the same sample, and the average value was taken as the charge amount. The charge amount is calculated from the following formula. The toner used for the measurement was "RICOH SP Toner Cyan C840" made by Ricoh Co., Ltd. The measurement environment was a temperature of 25°C and a relative humidity of 50%. Charge amount (μC / g) = measured charge (nC) x 10 3 × coefficient (1.0083×10 -3 ) ÷ toner weight (Wherein, toner weight=(weight before suction (g)−weight after suction (g)))

[0015] In addition, unless otherwise specified, the symbol "to" used in this specification is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit. Effect of the Invention

[0016] According to the carrier core material of the present invention, development memory is suppressed, and a decrease in the amount of developer picked up by the developing roller and the amount of developer transported to the developing area is suppressed.

[0017] Furthermore, by using a developer containing the carrier core material according to the present invention, it is possible to stably form images of good quality even after long-term use. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of a developing device using a carrier according to the present invention.

Mode for Carrying Out the Invention

[0019] One of the major features of the carrier core material according to the present invention is that it has a composition represented by (Mn x Mg y )Fe 3-(x+y) O4 (where 0.1 < x ≤ 1 and 0.1 < y ≤ 1), and calcium is contained in a range of more than 0.10 mol% and less than 1.0 mol% with respect to the total number of moles of Mn (manganese), Mg (magnesium), and Fe (iron). By containing calcium in the above amount, the electrical characteristics, magnetic characteristics, and shape characteristics of the carrier core material can be adjusted to a desired range. As a specific example, when calcium is contained in the above amount, the electrical resistance increases and the charge amount of the carrier core material increases.

[0020] Another major feature of the carrier core material according to the present invention is that the charge amount of the carrier core material is 18 μC / g or more. When the charge amount of the carrier core material is 18 μC / g or more, although the mechanism is not yet clear, it is presumed that the change in the charge amount of the carrier over time is suppressed, the change in the bulk density of the developer is suppressed, and the decrease in the conveyance amount of the developer is suppressed. The preferable upper limit value of the charge amount of the carrier core material is 40 μC / g, and the more preferable upper limit value is 30 μC / g.

[0021] The apparent density AD (g / cm 3 ) of the carrier core material of the present invention is preferably in the range of 1.80 or more and 2.80 or less, and more preferably in the range of 2.00 or more and 2.50 or less.

[0022] Also, the fluidity FR (sec / 50 g) of the carrier core material of the present invention is preferably in the range of 20 or more and 50 or less, and more preferably in the range of 24 or more and 40 or less. When the fluidity FR is within this range, the stress between the particles constituting the carrier core material is small, and the wear of the resin coating layer is suppressed.

[0023] The volume average particle diameter (D 50) is preferably in the range of 20 μm to 60 μm, more preferably in the range of 25 μm to 40 μm. The ratio of the carrier core particles having a particle size of 22 μm or less is preferably 5.0% or less, more preferably 1.5% or less.

[0024] The electrical resistance of the carrier core material of the present invention at a voltage of 1000 V is 5.0×10 5 It is preferably Ω or more, and more preferably 1.0×10 9 Ω or more. Electrical resistance is 5.0×10 5 By setting the electric resistance to Ω or more, charge injection into the carrier core material is effectively suppressed, and carrier adhesion is suppressed. Note that this electric resistance value is determined by the method for measuring static electric resistance in the examples described later.

[0025] The magnetic properties of the carrier core material of the present invention are preferably in the following ranges. These magnetic properties are measured by the method of measuring the magnetic properties in the examples described later. First, the saturation magnetization σ s (Am 2 / kg) is preferably in the range of 40 to 90, more preferably in the range of 55 to 70. s 90Am 2 If the toner density exceeds 100 / kg, the magnetic brush formed on the outer periphery of the developing roller becomes hard and the density of the magnetic brush becomes low, which may result in an insufficient amount of developer being transported to the developing area.

[0026] Also, the magnetic field is 79.58×10 3 Magnetization σ when A / m (1,000 Oersted) is applied 1k (Am 2 / kg) is preferably in the range of 30 to 80, more preferably in the range of 45 to 65. r (Am 2 / kg) is preferably in the range of 0.1 to 4.0, more preferably in the range of 0.1 to 2.5. r If is too small, the amount of developer picked up by the developing roller may decrease, while the residual magnetization σ rIf the retention force H is too large, it may be difficult to separate the carrier from the developing roller. c (×10 3 / (4π)A / m) is preferably in the range of 1.0 or more and 25.0 or less.

[0027] The shape characteristics of the carrier core material of the present invention are preferably in the following ranges. First, the maximum peak-valley depth Rz (μm) of the particles is preferably 1.4 μm or more. By having the maximum peak-valley depth Rz of 1.4 μm or more, development memory and insufficient developer transport amount are easily suppressed. The upper limit of the maximum peak-valley depth Rz of the particles is preferably 3.0 μm, and more preferably 2.1 μm.

[0028] The average length RSm (μm) of the carrier core material is preferably in the range of 4.0 to 10.0, more preferably in the range of 5.0 to 8.0, and the skewness Rsk of the carrier core material is preferably in the range of -0.50 to 0.00, more preferably in the range of -0.40 to -0.05.

[0029] The pore volume PV (cm) of the carrier core material according to the present invention 3 / g) is preferably in the range of 0.002 or more and 0.100 or less, and more preferably in the range of 0.002 or more and 0.040 or less. If the pore volume PV is too small, the amount of developer pumped up to the developing roller may decrease, while if the pore volume PV is too large, the magnetization per particle of the carrier core material may decrease, causing new problems such as carrier adhesion.

[0030] The BET specific surface area (m 2 The true density (g / cm3 / g) of the carrier core material of the present invention is preferably in the range of 0.03 to 0.50, more preferably in the range of 0.04 to 0.30. 3 ) is preferably in the range of 4.2 or more and 5.2 or less, and more preferably in the range of 4.5 or more and 4.9 or less.

[0031] The dielectric breakdown voltage BD (V) of the carrier core material of the present invention is preferably 2000 or more.

[0032] Although there is no particular limitation on the method for producing the carrier core material of the present invention, the production method described below is preferable.

[0033] First, Fe component raw material, Mn component raw material, Mg component raw material, Ca component raw material, and conventionally known additives are weighed out as necessary. As the Fe component raw material, Fe2O3, etc. can be used. As the Mn component raw material, MnCO3, Mn3O4, etc. can be used. As the Mg component raw material, MgCO3, Mg3O4, etc. can be used. Also, as the Ca component raw material, CaCO3, Ca(NO3)2, etc. can be used.

[0034] Next, the raw materials are put into the dispersion medium to prepare a slurry. Water is suitable as the dispersion medium used in the present invention. In addition to the above-mentioned calcination raw materials, a binder, a dispersant, etc. may be mixed into the dispersion medium as necessary. For example, polyvinyl alcohol can be used as the binder. The amount of the binder to be mixed is preferably about 0.1% by mass to 2% by mass in the slurry. In addition, for example, ammonium polycarboxylate or methacrylic acid-based polymer can be used as the dispersant. The amount of the dispersant to be mixed is preferably about 0.1% by mass to 2% by mass in the slurry. In addition, a reducing agent such as carbon black, a pH adjuster such as ammonia, a lubricant, a sintering accelerator, etc. may be mixed. The solid content concentration of the slurry is preferably in the range of 50% by mass to 90% by mass. More preferably, it is 60% by mass to 80% by mass. If it is 60% by mass or more, there are few pores in the particles in the granulated product, and insufficient sintering during firing can be prevented.

[0035] The weighed raw materials may be mixed, calcined, and deagglomerated, and then added to a dispersion medium to prepare a slurry. The calcination temperature is preferably in the range of 750°C to 1000°C. If it is 750°C or higher, partial ferritization by calcination proceeds, the amount of gas generated during calcination is small, and solid-state reactions proceed sufficiently, which is preferable. On the other hand, if it is 1000°C or lower, sintering by calcination is weak, and the raw materials can be sufficiently pulverized in the subsequent slurry pulverization process, which is preferable. In addition, air is preferable as the atmosphere during calcination.

[0036] Next, the slurry prepared as described above is wet-pulverized. For example, wet-pulverization is performed for a predetermined time using a ball mill or a vibration mill. The average particle size of the raw material after pulverization is preferably 5 μm or less, more preferably 1 μm or less. It is preferable that media of a predetermined particle size is contained inside the vibration mill or ball mill. Examples of the media material include iron-based chrome steel and oxide-based zirconia, titania, alumina, etc. The form of the pulverization process may be either continuous or batchwise. The particle size of the pulverized product is adjusted by the pulverization time, rotation speed, material and particle size of the media used, etc.

[0037] The pulverized slurry is then spray-dried to form granules. Specifically, the slurry is introduced into a spray dryer, such as a spray drier, and sprayed into the atmosphere to form spherical granules. The atmospheric temperature during spray drying is preferably in the range of 100°C to 300°C. This results in spherical granules with a particle size of 10 μm to 200 μm. Next, if necessary, the obtained granules are classified using a vibrating sieve to produce granules with a predetermined particle size range.

[0038] Next, the granulated material is put into a furnace heated to a predetermined temperature and sintered by a general method for synthesizing ferrite particles to generate ferrite particles. The sintering temperature is preferably in the range of 1050°C to 1350°C. More preferably, it is in the range of 1100°C to 1250°C. If the sintering temperature is 1050°C or lower, phase transformation is unlikely to occur and sintering is unlikely to proceed. If the sintering temperature exceeds 1350°C, excessive sintering may cause excessive grains to be generated. The heating rate up to the sintering temperature is preferably in the range of 250°C / h to 500°C / h. The holding time at the sintering temperature is preferably 2 hours or more. The unevenness of the ferrite particle surface can also be adjusted by the oxygen concentration in the sintering process. Specifically, the oxygen concentration is set to 0.05% to 10%. Also, the oxidation state of the ferrite phase may be adjusted by setting the oxygen concentration during cooling lower than the oxygen concentration during sintering. Specifically, the oxygen concentration is set to the range of 0.05% to 21%. The oxygen concentration during the heating, sintering and cooling steps is preferably controlled within the range of 0.05% to 21%. The oxygen concentration during the heating step is more preferably within the range of 0.6% to 5%.

[0039] The fired product thus obtained is disintegrated as necessary. Specifically, for example, the fired product is disintegrated by a hammer mill or the like. The disintegration process may be either continuous or batchwise. After the disintegration process, classification may be performed to adjust the particle size to a predetermined range as necessary. As a classification method, a conventionally known method such as wind classification or sieve classification may be used. After primary classification by a wind classifier, the particle size may be adjusted to a predetermined range by a vibrating sieve or ultrasonic sieve. Furthermore, after the classification process, non-magnetic particles may be removed by a magnetic field separator. The particle size of the ferrite particles is preferably 25 μm or more and less than 50 μm.

[0040] Thereafter, if necessary, the classified ferrite particles may be heated in an oxidizing atmosphere to form an oxide film on the particle surface to increase the resistance of the ferrite particles (resistance-increasing treatment). The oxidizing atmosphere may be either an air atmosphere or a mixed atmosphere of oxygen and nitrogen. The heating temperature is preferably in the range of 200°C to 800°C, more preferably in the range of 360°C to 550°C. The heating time is preferably in the range of 0.5 hours to 5 hours. From the viewpoint of homogenizing the surface and the interior of the ferrite particles, a low heating temperature is desirable.

[0041] The ferrite particles prepared as described above are used as the carrier core material of the present invention. In order to obtain the desired charging properties, the outer periphery of the carrier core material is coated with a resin to form a carrier for electrophotographic development.

[0042] The resin that coats the surface of the carrier core material may be any of the conventionally known resins, such as polyethylene, polypropylene, polyvinyl chloride, poly-4-methylpentene-1, polyvinylidene chloride, ABS (acrylonitrile-butadiene-styrene) resin, polystyrene, (meth)acrylic resins, polyvinyl alcohol resins, as well as thermoplastic elastomers such as polyvinyl chloride, polyurethane, polyester, polyamide, and polybutadiene, and fluorosilicone resins.

[0043] To coat the surface of the carrier core material with a resin, a solution or dispersion of the resin may be applied to the carrier core material. As the solvent for the coating solution, one or more of the following may be used: aromatic hydrocarbon solvents such as toluene and xylene; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; cyclic ether solvents such as tetrahydrofuran and dioxane; alcohol solvents such as ethanol, propanol, and butanol; cellosolve solvents such as ethyl cellosolve and butyl cellosolve; ester solvents such as ethyl acetate and butyl acetate; and amide solvents such as dimethylformamide and dimethylacetamide. The resin component concentration in the coating solution is generally in the range of 0.001% by mass to 30% by mass, particularly 0.001% by mass to 2% by mass.

[0044] The resin can be coated onto the carrier core material by, for example, a spray-drying method, a fluidized bed method, a spray-drying method using a fluidized bed, a dipping method, etc. Among these, the fluidized bed method is particularly preferred because it can be efficiently coated with a small amount of resin. In the case of the fluidized bed method, for example, the amount of resin coating can be adjusted by the amount of resin solution sprayed and the spraying time.

[0045] The particle size of the carrier is generally preferably in the range of 20 μm or more and less than 60 μm, particularly preferably in the range of 25 μm or more and 40 μm or less, in terms of volume average particle size.

[0046] The electrophotographic developer according to the present invention is obtained by mixing the carrier and toner prepared as described above. There is no particular limitation on the mixture ratio of the carrier and toner, and it may be appropriately determined based on the development conditions of the developing device to be used. In general, the toner concentration in the developer is preferably in the range of 1% by mass or more and 15% by mass or less. If the toner concentration is less than 1% by mass, the image density becomes too thin, while if the toner concentration exceeds 15% by mass, toner scattering occurs in the developing device, which may cause problems such as dirt inside the device or toner adhesion to the background part of the transfer paper. A more preferable toner concentration is in the range of 3% by mass or more and 10% by mass or less.

[0047] The toner may be produced by a conventional method such as a polymerization method, a pulverization classification method, a melt granulation method, a spray granulation method, etc. Specifically, a toner containing a colorant, a release agent, a charge control agent, etc. in a binder resin mainly composed of a thermoplastic resin can be suitably used.

[0048] Generally, the particle size of the toner is preferably in the range of 5 μm to 15 μm, more preferably 7 μm to 12 μm, in terms of the volume average particle size measured by a Coulter counter.

[0049] If necessary, a modifier may be added to the toner surface. Examples of the modifier include silica, alumina, zinc oxide, titanium oxide, magnesium oxide, polymethyl methacrylate, etc. These may be used alone or in combination of two or more.

[0050] The carrier and toner can be mixed using a conventionally known mixing device, such as a Henschel mixer, a V-type mixer, a tumbler mixer, or a hybridizer.

[0051] Although there is no particular limitation on the developing method using the developer of the present invention, a magnetic brush development method is preferable. Fig. 1 shows a schematic diagram of an example of a developing device that performs magnetic brush development. The developing device shown in Fig. 1 includes a rotatable developing roller 3 incorporating a plurality of magnetic poles, a regulating blade 6 that regulates the amount of developer on the developing roller 3 that is transported to a developing section, two screws 1 and 2 that are arranged in parallel in the horizontal direction and stir and transport the developer in opposite directions, and a partition plate 4 that is formed between the two screws 1 and 2 and allows the developer to move from one screw to the other screw at both ends of the screws and prevents the developer from moving at any other than both ends.

[0052] The two screws 1 and 2 have helical blades 13 and 23 formed on shafts 11 and 21 at the same inclination angle, and are rotated in the same direction by a driving mechanism (not shown) to transport the developer in opposite directions. The developer moves from one screw to the other at both ends of the screws 1 and 2. This causes the developer, which is made up of toner and carrier, to constantly circulate and be stirred inside the device.

[0053] Meanwhile, the developing roller 3 is a metal cylindrical body with a surface roughness of several μm, and has a fixed magnet with five magnetic poles arranged in order as magnetic pole generating means: a developing magnetic pole N1, a transporting magnetic pole S1, a peeling magnetic pole N2, a pumping magnetic pole N3, and a blade magnetic pole S2. When the cylindrical body of the developing roller 3 rotates in the direction of the arrow, the developer is pumped up from the screw 1 to the developing roller 3 by the magnetic force of the pumping magnetic pole N3. The developer carried on the surface of the developing roller 3 is regulated in layer by a regulating blade 6, and then transported to the development area.

[0054] In the development area, a bias voltage in which an AC voltage is superimposed on a DC voltage is applied from a transfer voltage power source 8 to the development roller 3. The DC voltage component of the bias voltage is set to a potential between the background portion potential and the image portion potential on the surface of the photoconductor drum 5. The background portion potential and the image portion potential are set to potentials between the maximum and minimum values ​​of the bias voltage. The peak-to-peak voltage of the bias voltage is preferably in the range of 0.5 kV to 5 kV, and the frequency is preferably in the range of 1 kHz to 10 kHz. The waveform of the bias voltage may be any of a square wave, a sine wave, a triangular wave, and the like. This causes the toner and carrier to vibrate in the development area, and the toner adheres to the electrostatic latent image on the photoconductor drum 5 to develop it.

[0055] The developer on the developing roller 3 is then transported inside the device by the transport magnetic pole S1, peeled off from the developing roller 3 by the peeling electrode N2, and circulated again within the device by the screws 1 and 2, where it is mixed and stirred with the developer not being used for development. Then, new developer is supplied from the screw 1 to the developing roller 3 by the pumping pole N3.

[0056] In the embodiment shown in FIG. 1, the developing roller 3 has five magnetic poles. However, it is of course possible to increase the number of magnetic poles to eight, ten, or twelve in order to increase the amount of developer movement in the development area or to further improve the pumping performance, etc. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0058] Example 1 As raw materials, 9.76 kg of Fe2O3 (average particle size: 0.6 μm) and 2.24 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pre-fired raw material was obtained by pulverizing for 6 hours using a dry bead mill. The pre-fired powder obtained was dispersed in 7.98 kg of water, and 6.40 kg of Fe2O3 (average particle size: 0.6 μm), 3.11 kg of Mn3O4 (average particle size: 2 μm), 156.4 g of CaCO3, and 236.3 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content concentration in this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 g. 50 is 1.0μm, cumulative distribution 90% particle size D 90 was 3.8 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 35.9 μm. The apparent density, fluidity, volume average particle size (average particle size), magnetic properties, pore volume, BET specific surface area, static electrical resistance, and true density of the obtained carrier core material were measured by the methods described below. The measurement results are shown in Tables 1 and 2. The physical properties of the carrier core materials in the following examples and comparative examples were also measured by the same methods.

[0059] Example 2 The carrier core material obtained in Example 1 was subjected to an oxidation treatment by being held at a temperature of 400° C. in the atmosphere for 1 hour, and a carrier core material according to Example 2 was obtained.

[0060] Example 3 The carrier core material obtained in Example 1 was subjected to an oxidation treatment by being held at a temperature of 420° C. in the atmosphere for 1 hour, and a carrier core material according to Example 3 was obtained.

[0061] Example 4 The carrier core material obtained in Example 1 was subjected to an oxidation treatment by being held at a temperature of 440° C. in the atmosphere for 1 hour, and a carrier core material according to Example 4 was obtained.

[0062] Example 5 The carrier core material obtained in Example 1 was subjected to an oxidation treatment by being held at a temperature of 460° C. in the atmosphere for 1 hour, and a carrier core material according to Example 5 was obtained.

[0063] Example 6 The carrier core material obtained in Example 1 was subjected to an oxidation treatment by being held at a temperature of 480° C. in the atmosphere for 1 hour, and a carrier core material according to Example 6 was obtained.

[0064] reference Example 7 As raw materials, 8.13 kg of Fe2O3 (average particle size: 0.6 μm) and 1.87 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 8.12 kg of water, and 7.99 kg of Fe2O3 (average particle size: 0.6 μm), 3.89 kg of Mn3O4 (average particle size: 2 μm), 159.7 g of CaCO3, and 240.3 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 g. 50 is 1.1μm, cumulative distribution 90% particle size D 90 was 6.1 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 35.7 μm.

[0065] reference Example 8 reference The carrier core material obtained in Example 7 was subjected to an oxidation treatment by being held at a temperature of 400° C. in the atmosphere for 1 hour. reference A carrier core material according to Example 8 was obtained.

[0066] reference Example 9 reference The carrier core material obtained in Example 7 was subjected to an oxidation treatment by being held at a temperature of 420° C. in the atmosphere for 1 hour. reference A carrier core material according to Example 9 was obtained.

[0067] reference Example 10 referenceThe carrier core material obtained in Example 7 was subjected to an oxidation treatment by being held at a temperature of 440° C. in the atmosphere for 1 hour. reference A carrier core material according to Example 10 was obtained.

[0068] reference Example 11 reference The carrier core material obtained in Example 7 was subjected to an oxidation treatment by being held at a temperature of 460° C. in the atmosphere for 1 hour. reference A carrier core material according to Example 11 was obtained.

[0069] reference Example 12 reference The carrier core material obtained in Example 7 was subjected to an oxidation treatment by being held at a temperature of 480° C. in the atmosphere for 1 hour. reference A carrier core material according to Example 12 was obtained.

[0070] Example 13 As raw materials, 6.50 kg of Fe2O3 (average particle size: 0.6 μm) and 1.50 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 8.25 kg of water, and 9.56 kg of Fe2O3 (average particle size: 0.6 μm), 4.66 kg of Mn3O4 (average particle size: 2 μm), 162.8 g of CaCO3, and 244.1 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 g. 50 is 1.1μm, cumulative distribution 90% particle size D 90 was 5.1 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 36.2 μm.

[0071] Example 14 The carrier core material obtained in Example 13 was subjected to an oxidation treatment by being held at a temperature of 400° C. in the atmosphere for 1 hour, and a carrier core material according to Example 14 was obtained.

[0072] Example 15 The carrier core material obtained in Example 13 was subjected to an oxidation treatment by being held at a temperature of 420° C. in the atmosphere for 1 hour, and a carrier core material according to Example 15 was obtained.

[0073] Example 16 The carrier core material obtained in Example 13 was subjected to an oxidation treatment by being held at a temperature of 440° C. in the atmosphere for 1 hour, and a carrier core material according to Example 16 was obtained.

[0074] Example 17 The carrier core material obtained in Example 13 was subjected to an oxidation treatment by being held at a temperature of 460° C. in the atmosphere for 1 hour, and a carrier core material according to Example 17 was obtained.

[0075] Example 18 The carrier core material obtained in Example 13 was subjected to an oxidation treatment by being held at a temperature of 480° C. in the atmosphere for 1 hour, and a carrier core material according to Example 18 was obtained.

[0076] Example 19 As raw materials, 14.34 kg of Fe2O3 (average particle size: 0.6 μm), 4.62 kg of Mn3O4 (average particle size: 2 μm), and 1.04 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 7.12 kg of water, to which 149.5 g of CaCO3 and 219.7 g of a solution containing 50% polycarboxylate ammonium dispersant were added, and the mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 kg. 50 is 1.5μm, cumulative distribution 90% particle size D 90 was 5.3 μm. This mixed slurry was sprayed into hot air at about 220° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 35.6 μm.

[0077] Example 20 As raw materials, 28.68 kg of Fe2O3 (average particle size: 0.6 μm), 9.24 kg of Mn3O4 (average particle size: 2 μm), and 2.08 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 14.85 kg of water, and 299.0 g of CaCO3 and 439.4 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.0 kg. 50 is 1.6μm, cumulative distribution 90% particle size D 90 was 6.3 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 35.7 μm.

[0078] Example 21 The carrier core material obtained in Example 20 was subjected to an oxidation treatment by being held at a temperature of 420° C. in the atmosphere for 1 hour, and a carrier core material according to Example 21 was obtained.

[0079] Example 22 The carrier core material obtained in Example 20 was subjected to an oxidation treatment by being held at a temperature of 440° C. in the atmosphere for 1 hour, and a carrier core material according to Example 22 was obtained.

[0080] Example 23 The carrier core material obtained in Example 20 was subjected to an oxidation treatment by being held at a temperature of 460° C. in the atmosphere for 1 hour, and a carrier core material according to Example 23 was obtained.

[0081] Example 24 The carrier core material obtained in Example 20 was subjected to an oxidation treatment by being held at a temperature of 480° C. in the atmosphere for 1 hour, and a carrier core material according to Example 24 was obtained.

[0082] Example 25 As raw materials, 18.64 kg of Fe2O3 (average particle size: 0.6 μm), 6.01 kg of Mn3O4 (average particle size: 2 μm), and 1.35 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were calcined in a rotary calciner at 850 °C under atmospheric conditions. The mixture was pulverized in a dry bead mill for 6 hours to obtain a calcined raw material. The calcined powder obtained was dispersed in 14.71 kg of water, and 295.6 g of CaCO3 and 435.4 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 g. 50 is 1.1μm, cumulative distribution 90% particle size D 90 was 5.2 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 36.0 μm.

[0083] Example 26 The carrier core material obtained in Example 25 was subjected to an oxidation treatment by being held at a temperature of 420° C. in the atmosphere for 1 hour, and a carrier core material according to Example 26 was obtained.

[0084] Example 27 The carrier core material obtained in Example 25 was subjected to an oxidation treatment by being held at a temperature of 440° C. in the atmosphere for 1 hour, and a carrier core material according to Example 27 was obtained.

[0085] Example 28 The carrier core material obtained in Example 25 was subjected to an oxidation treatment by being held at a temperature of 460° C. in the atmosphere for 1 hour, and a carrier core material according to Example 28 was obtained.

[0086] Example 29 The carrier core material obtained in Example 25 was subjected to an oxidation treatment by being held at a temperature of 480° C. in the atmosphere for 1 hour, to obtain a carrier core material according to Example 29.

[0087] Example 30 As raw materials, 28.68 kg of Fe2O3 (average particle size: 0.6 μm), 9.24 kg of Mn3O4 (average particle size: 2 μm), and 2.08 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 14.85 kg of water, and 217.5 g of CaCO3 and 439.4 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 g. 50 is 1.5μm, cumulative distribution 90% particle size D 90 was 6.1 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 36.2 μm.

[0088] Example 31 As raw materials, 28.68 kg of Fe2O3 (average particle size: 0.6 μm), 9.24 kg of Mn3O4 (average particle size: 2 μm), and 2.08 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 14.78 kg of water, to which 108.7 g of CaCO3 and 439.4 g of a solution containing 50% polycarboxylate ammonium dispersant were added, and the mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 g. 50 is 1.6μm, cumulative distribution 90% particle size D 90 was 6.1 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 35.6 μm.

[0089] Example 32 Carrier core particles having an average particle size of 35.2 μm were obtained in the same manner as in Example 19, except that the firing temperature was 1250° C., the holding time was 4.5 hours, and then cooling was performed over 9 hours at an oxygen concentration of 0.75%.

[0090] reference Example 33 A carrier core material having an average particle size of 39.4 μm was obtained in the same manner as in Example 32, except that the obtained fired product was disintegrated and then classified using a sieve.

[0091] reference Example 34 A carrier core material having an average particle size of 44.0 μm was obtained in the same manner as in Example 32, except that the obtained fired product was disintegrated and then classified using a sieve.

[0092] Example 35 The carrier core material obtained in Example 32 was subjected to an oxidation treatment by being held at a temperature of 360° C. in the atmosphere for 1 hour, thereby obtaining a carrier core material according to Example 35.

[0093] Comparative Example 1 As raw materials, 9.18 kg of Fe2O3 (average particle size: 0.6 μm), 2.96 kg of Mn3O4 (average particle size: 2 μm), and 0.67 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 14.63 kg of water, and 293.2 g of CaCO3 and 432.9 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.0 kg. 50 is 1.0μm, cumulative distribution 90% particle size D 90 was 5.7 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 36.2 μm.

[0094] Comparative Example 2 The carrier core material obtained in Comparative Example 1 was subjected to an oxidation treatment by being held at a temperature of 420° C. in the atmosphere for 1 hour, and a carrier core material according to Comparative Example 2 was obtained.

[0095] Comparative Example 3 The carrier core material obtained in Comparative Example 1 was subjected to an oxidation treatment by being held at a temperature of 440° C. in the atmosphere for 1 hour, and a carrier core material according to Comparative Example 3 was obtained.

[0096] Comparative Example 4 The carrier core material obtained in Comparative Example 1 was subjected to an oxidation treatment by being held at a temperature of 460° C. in the atmosphere for 1 hour, and a carrier core material according to Comparative Example 4 was obtained.

[0097] Comparative Example 5 The carrier core material obtained in Comparative Example 1 was subjected to an oxidation treatment by being held at a temperature of 480° C. in the atmosphere for 1 hour, and a carrier core material according to Comparative Example 5 was obtained.

[0098] Comparative Example 6 As raw materials, 28.68 kg of Fe2O3 (average particle size: 0.6 μm), 9.24 kg of Mn3O4 (average particle size: 2 μm), and 2.08 kg of MgO were mixed. This mixture was pelletized using a roller compactor. The obtained pellets were pre-fired in a rotary firing furnace at 850 °C under atmospheric conditions. The pellets were pulverized for 6 hours using a dry bead mill to obtain a pre-fired raw material. The pre-fired powder obtained was dispersed in 14.76 kg of water, and 54.4 g of CaCO3 and 439.4 g of a solution containing 50% polycarboxylate ammonium dispersant were added. The mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 73.5%, and the cumulative distribution 50% particle size D of the raw materials in the slurry was 1.06 g. 50 is 1.6μm, cumulative distribution 90% particle size D 90 was 6.4 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at 1250°C for 3 hours. It was then cooled for 6 hours at an oxygen concentration of 0.75%. The sintered material was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 35.7 μm.

[0099] Comparative Example 7 As raw materials, 20.80 kg of Fe2O3 (average particle size: 0.6 μm) and 8.12 kg of Mn3O4 (average particle size: 2 μm) were dispersed in 11.50 kg of water, 180.0 g of polycarboxylate ammonium dispersant, 10.0 g of ammonia water as a pH adjuster, and 63.0 g of carbon black as a reducing agent were added, and the mixture was pulverized in a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. The solid content of this slurry was 75%, and the cumulative distribution of the raw materials in the slurry at 50% particle size D 50 is 0.6μm, cumulative distribution 90% particle size D 90 was 1.5 μm. This mixed slurry was sprayed into hot air at about 130° C. using a spray dryer to obtain a dried granulated powder. At this time, granulated powders other than those having the desired particle size distribution were removed using a sieve. The granulated powder was placed in an electric sintering furnace and sintered at a temperature of 1200°C for 2.5 hours. It was then cooled at an oxygen concentration of 1.30% for 5.5 hours. The sintered product was degranulated and classified using a sieve to obtain a carrier core material with an average particle size of 34.0 μm. The obtained carrier core material was subjected to an oxidation treatment by being held at a temperature of 410°C in the atmosphere for 1 hour, to obtain a carrier core material according to Comparative Example 7.

[0100] (Apparent Density (AD)) The apparent density of the carrier core material was measured in accordance with JIS Z 2504.

[0101] (Flow rate (FR)) The fluidity of the carrier core material was measured in accordance with JIS Z 2502.

[0102] (Volume average particle size (D 50 ) and percentage of particles with a particle size of 22 μm or less (%) The volume average particle size of the carrier core material was measured using a laser diffraction particle size distribution measuring device ("Microtrac Model 9320-X100" manufactured by Nikkiso Co., Ltd.).

[0103] (Magnetic properties) Using a room temperature dedicated vibrating sample magnetometer (VSM) ("VSM-P7" manufactured by Toei Kogyo Co., Ltd.), the external magnetic field was set to 0 to 79.58 × 10 4 A / m (10,000 Oersted) is continuously applied for one cycle to measure the saturation magnetization σ s , residual magnetization σ r , holding force H c and magnetic field 79.58×10 3 Magnetization σ when A / m (1,000 Oersted) is applied 1k (Am 2 / kg) was measured.

[0104] (Static Electrical Resistance) Two 2 mm thick brass plates with electrolytically polished surfaces were used as electrodes, arranged with a distance of 2 mm between the electrodes. 200 mg of carrier core material was placed in the gap between the two electrodes, and then a 240 mm diameter copper foil was placed behind each electrode. 2 A magnet was placed between the electrodes to form a bridge of the powder to be measured, and DC voltages of 100V, 500V, and 1000V were applied between the electrodes, and the current flowing through the carrier core material was measured by the four-terminal method to obtain the resistance. (The current value and the resistance at an electrode distance of 2 mm and a cross-sectional area of ​​240 mm were also calculated.) 2 From this, the volume resistivity of the static electrical resistance of the carrier core material can also be calculated.)

[0105] (Rechargeable Electrical Resistance) Cross-sectional area 1.3cm 2 A brass bottom plate electrode was placed on the bottom of a vinyl chloride cylindrical pipe (radius 0.643 cm), and 5 g of a weighed sample was added. The brass cylindrical electrode was then inserted from the top of the pipe, and the sample was sandwiched between the brass bottom plate electrode and the brass cylindrical electrode. The difference in the mutation sensor value was then calculated from the end position of the brass cylindrical electrode before and after the sample was filled, and was taken as the thickness of the sample layer. Then, DC voltages of 100 V, 250 V, 500 V, 750 V, and 1000 V were applied between the electrodes with the sample filled, and the resistance value of the carrier core material was measured using an insulation resistance meter (Toa Denpa Kogyo, Type SM-8215). The specific resistance was then calculated from the following formula. Resistivity (Ω cm) = insulation resistance meter value (Ω) × cross-sectional area of ​​sample layer (cm2 ) ÷ sample layer thickness (cm)

[0106] (Breakdown voltage, BD) Two 2 mm thick brass plates with electrolytically polished surfaces were used as electrodes, arranged with a distance of 2 mm between the electrodes. 200 mg of carrier was placed in the gap between the two electrodes, and then a 240 mm square tube with a cross-sectional area was placed behind each electrode. 2 With the magnets arranged to form a bridge of the powder to be measured between the electrodes, a DC voltage was applied between the electrodes in steps of 100V to 2000V in 100V increments, and the voltage at which the current value exceeded 100mA was taken as the breakdown voltage. If the current value did not exceed 100mA at 2000V, the breakdown voltage was taken as 2000V.

[0107] (Pore volume) The evaluation device used was a POREMASTER-60GT manufactured by Quantachrome. Specifically, the measurement conditions were as follows: Cell Stem Volume: 0.5cm 3 , Head pressure: 20PSIA, Surface tension of mercury: 485.00 erg / cm 2 , Contact angle of mercury: 130.00degrees, High pressure measurement mode: Fixed Rate, Motor Speed: 1, High pressure measurement range: 20.00~10000.00PSI A 1,500 g sample was weighed and measured to determine the distance between the sample and 0.5 cm 3 (cc) cell was filled and the measurement was performed. Also, the volume B (cm 3 / g) to volume A at 60 PSI (cm 3 The value obtained by subtracting the pore volume (1 / g) was taken as the pore volume.

[0108] (BET specific surface area) Using a BET single-point specific surface area measuring device (Mountec Co., Ltd., model: Macsorb HM model-1208), 5.00 g of sample was measured with a volume of 5 cm 3The mixture was filled in a cell and degassed at 200°C for 30 minutes before measurement.

[0109] (true density) The true density of the carrier core material was measured using "ULTRA PYCNOMETER 1000" manufactured by Quantachrome.

[0110] (Maximum peak-valley depth Rz, average length RSm, skewness Rsk) The surface was observed with a 100x objective lens using an ultra-deep color 3D shape measuring microscope ("VK-X100" manufactured by Keyence Corporation). Specifically, ferrite particles were first fixed to a flat adhesive tape with a surface, and the measurement field of view was determined with a 100x objective lens, after which the focus was adjusted to the adhesive tape surface using the autofocus function. A laser beam was irradiated from the vertical direction (Z direction) onto the flat adhesive tape surface on which the ferrite particles were fixed, and the surface was scanned in the X and Y directions. In addition, data in the Z direction was obtained by connecting the lens height positions when the intensity of the reflected light from the surface was at its maximum. The position data in the X, Y, and Z directions were connected to obtain the 3D shape of the ferrite particle surface. The auto-photography function was used to capture the 3D shape of the ferrite particle surface. Each parameter was measured using particle roughness inspection software (manufactured by Mitani Shoji). First, as a pretreatment, particle recognition and shape selection were performed on the three-dimensional shape of the obtained ferrite particle surface. Particle recognition was performed in the following manner. Of the three-dimensional shape obtained by photography, the maximum value in the Z direction was set to 100%, the minimum value was set to 0%, and the range between the maximum value and the minimum value was divided into 100 equal parts. The region corresponding to 100 to 35% was extracted, and the outline of the independent region was recognized as the particle outline. Next, particles such as coarse, small, and associated particles were excluded by shape selection. By performing this shape selection, it is possible to reduce errors during the curvature correction performed later. Specifically, particles with an area equivalent diameter of 28 μm or less, 38 μm or more, and an acicular ratio of 1.15 or more were excluded. In addition, for Example 33, D 50 In accordance with the above, particles with an area-equivalent diameter of 35 μm or less, 45 μm or more, and an acicular ratio of 1.15 or more were excluded. 50In accordance with this, particles with an area-equivalent diameter of 40 μm or less, 50 μm or more, and an acicular ratio of 1.15 or more were excluded. Here, the acicular ratio is a parameter calculated from the ratio of the maximum length of the particle to the diagonal width, and the diagonal width represents the shortest distance between two straight lines parallel to the maximum length when the particle is sandwiched between them. Next, the portion to be used for analysis was extracted from the three-dimensional surface shape. First, a 15.0 μm square was drawn with the center of gravity determined from the particle outline recognized by the above method as its center. 21 parallel lines were drawn within the square, and 21 roughness curves that fell on those line segments were extracted. Since the carrier core material is approximately spherical, the roughness curve has a certain curvature as the background. Therefore, to correct the background, an optimal quadratic curve was fitted and subtracted from the roughness curve. In this case, a low-pass filter was applied with a strength of 1.5 μm, and the cutoff value λ was set to 80 μm.

[0111] The maximum peak-valley depth Rz was calculated as the sum of the height of the highest peak and the depth of the deepest valley in the roughness curve. The measurement of the maximum height Rz described above was performed in accordance with JIS B0601 (2001 edition). The maximum height Rz was calculated using the average value of 50 particles as the average value of each parameter.

[0112] The average length RSm is calculated by averaging the length of each element, with a combination of a valley and a peak in the roughness curve defined as one element. The measurement of the average length RSm described above is performed in accordance with JIS B0601 (2001 edition). The average value of 50 particles is used to calculate the average length RSm for each parameter.

[0113] (Skewness Rsk) The skewness Rsk was calculated by applying the roughness curve to the following formula 1.

[0114]

number

[0115] Here, in the formula 1, Rn represents the difference from the average line of the nth peak or valley in a reference length of 15 μm, and the root mean square height Rq is calculated by the formula shown in the following formula 2.

[0116]

number

[0117] Here, the larger the value of the obtained skewness Rsk, the more biased it is toward the valley region.

[0118] (Development memory) The surface of the obtained carrier core material was coated with resin to prepare a carrier. Specifically, 450 parts by mass of silicone resin and 9 parts by mass of (2-aminoethyl)aminopropyltrimethoxysilane were dissolved in 450 parts by mass of toluene as a solvent to prepare a coating solution. This coating solution was applied to 50,000 parts by mass of the carrier core material using a fluidized bed type coating device, and heated in an electric furnace at a temperature of 300°C to obtain a carrier. In the following, carriers were obtained in the same manner for all examples and comparative examples. The obtained carrier and toner having an average particle size of about 5.0 μm were mixed for a predetermined time using a pot mill to obtain a two-component electrophotographic developer. In this case, the carrier and toner were adjusted so that the weight of the toner / (weight of the toner and carrier)=5 / 100. The developer was obtained in the same manner for all the following examples and comparative examples. The obtained developer was put into a developing device (peripheral speed of the developing roller Vs: 406 mm / sec, peripheral speed of the photosensitive drum Vp: 205 mm / sec, distance between the photosensitive drum and the developing roller: 0.3 mm) having a structure shown in FIG. 1, and an image in which a solid image portion and a non-image portion are adjacent to each other in the longitudinal direction of the photosensitive drum, followed by a wide area of ​​intermediate tones, was obtained initially and after 200,000 sheets of image formation, and the image density of the area where the solid image of the first rotation of the developing roller was developed and the area where it was not developed was measured using a reflection densitometer (model number TC-6D manufactured by Tokyo Denshoku Co., Ltd.), and the difference was obtained and evaluated according to the following criteria. "○": Less than 0.006 "△": 0.006 or more and less than 0.020 "×": 0.020 or more

[0119] (charge amount) 9.5g of carrier core material and 0.5g of toner from a commercially available full-color machine are placed in a 100ml glass bottle with a stopper, and left for 12 hours in an environment with a temperature of 25°C and a relative humidity of 50% to condition the humidity. The conditioned carrier core material and toner are mixed by shaking with a shaker for 30 minutes. Here, the shaker used was a NEW-YS type made by Yayoi Co., Ltd., and was performed at 200 times / min and an angle of 60°. 500mg of the mixed carrier core material and toner were weighed, and the charge was measured with a charge measuring device. The charge measuring device used was the "STC-1-C1 type" made by Nippon Piotek Co., Ltd., with a suction pressure of 5.0kPa and a suction mesh made of SUS 795mesh. Two measurements were taken for the same sample, and the average value was taken as the charge. The charge is calculated from the following formula. The toner used for the measurement was "RICOH SP Toner Cyan C840" made by Ricoh Co., Ltd. The measurement environment was a temperature of 25°C and a relative humidity of 50%. Charge amount (μC / g) = measured charge (nC) x 10 3 × coefficient (1.0083×10 -3 ) ÷ toner weight (Wherein, toner weight=(weight before suction (g)−weight after suction (g)))

[0120] (Decrease in transport volume) 80 g of the above-mentioned two-component electrophotographic developer (developer) was placed in a small developing device (roller diameter: 16 mm, grooved roller, non-magnetic regulating plate gap: 0.6 mm) and stirred for 3 minutes and 180 minutes at a roller rotation speed of 250 rpm. After that, a circular hole with an area of ​​3.785 cm2 and an area of ​​4 cm2 and 1 cm2 was cut out on the developing roller. 2 The developer in the patch was sucked and collected in the filter using a filter-equipped suction device. The weight of the filter before and after collection was measured, the weight difference of the filter was calculated, and the amount of developer transported per unit area was calculated using the following formula.

number

number

[0121] [Table 1]

[0122] [Table 2]

[0123] As shown in Tables 1 and 2, the carrier core materials of Examples 1, 7, 13, 19, 20, 25, 30, and 31 have different composition ratios. The carrier core materials of Examples 2 to 6, 8 to 12, 14 to 18, 21 to 24, and 26 to 29 have the same composition as the carrier core materials of the above-mentioned Examples, but are oxidized at different temperatures. The carrier core materials of Examples 32 to 34 have the same composition, but are different in average particle size, and the carrier core material of Example 35 is the carrier core material of Example 32 that has been oxidized.

[0124] In the resin-coated carriers using the carrier core materials of Examples 1 to 35, the rate of decrease in the amount of developer transported to the development area was less than 10%, which was good in all cases. In addition, regarding the development memory, the maximum peak-valley depth Rz of the particles was less than 1.4 μm. reference Examples 7 to 12 and reference Although slight development memory was observed in the resin-coated carriers using the carrier core materials of Examples 33 and 34, it was within a range that did not cause problems in practical use. Moreover, no development memory was observed in the resin-coated carriers using the carrier core materials of the other Examples.

[0125] In contrast, a drop in transport amount of 10% or more occurred in the resin-coated carriers using the carrier core materials of Comparative Examples 1 to 5, in which the charge amount was less than 18 μC / g. Also, a drop in transport amount of 10% or more occurred in the resin-coated carriers using the carrier core materials of Comparative Examples 6 and 7, in which the Ca content relative to the total molar number of Mn, Mg, and Fe was 0.10 mol% or less and the charge amount was less than 18 μC / g. [Industrial Applicability]

[0126] According to the carrier core material of the present invention, development memory can be suppressed, and a decrease in the amount of developer picked up by the developing roller and the amount of developer transported to the developing area is unlikely to occur. [Explanation of symbols]

[0127] 3 Developing roller 5 Photoconductor drum

Claims

1. A carrier core material used in a two-component developer comprising a toner and a resin-coated carrier in which a portion of the carrier core material is exposed on the surface, The toner used in the two-component developer and a carrier core material have a charge amount of 18 μC / g or more as measured by the following method, The carrier core material is composed of ferrite particles, (Mn x Mg y ) Fe 3-(x+y) O 4 (wherein 0.1<x≦1, 0.1<y≦1), Ca is contained in the range of more than 0.10 mol% and less than 1.0 mol% relative to the total mole number of Mn, Mg, and Fe, The maximum peak-valley depth Rz of the grain is 1.4 μm or more. A ferrite carrier core material comprising: (Measurement method) 9.5 g of carrier core material and 0.5 g of toner are placed in a 100 ml glass bottle with a stopper, and left for 12 hours in an environment of 25°C temperature and 50% relative humidity to condition the humidity. The conditioned carrier core material and toner are mixed by shaking with a shaker for 30 minutes. Here, shaking is performed at 200 times / min and an angle of 60°. 500 mg of the mixed carrier core material and toner are weighed, and the charge amount is measured with a charge amount measuring device. The suction pressure is 5.0 kPa, and a 795 mesh SUS suction mesh is used. The charge amount is calculated from the following formula. The measurement environment is 25°C temperature and 50% relative humidity. Charge amount (μC / g) = measured charge (nC) × 10 3 × coefficient (1.0083 × 10 -3 ) ÷ toner weight (Wherein, toner weight=(weight before suction (g)−weight after suction (g)))

2. 2. A carrier for electrophotographic development, comprising the ferrite carrier core material according to claim 1, the surface of which is coated with a resin.

Citation Information

Patent Citations

  • Amorphous ferrite carrier and electrophotographic developer using the ferrite carrier

    JP2007148452A

  • Carrier core material for electrophotographic developer, carrier for electrophotographic developer, and electrophotographic developer

    JP2012088385A

  • Method for producing carrier core material for electrophotographic developer, carrier core material for electrophotographic developer, carrier for electrophotographic developer, and electrophotographic developer

    JP2012177829A

  • Ferrite particle, carrier for developing electrophotography and developing agent for electrophotography using the same

    JP2017031031A